P143Targeting the mitochondrial fission proteins, MiD49 and MiD51, as a therapeutic strategy for cardioprotection. (15th July 2014) - Samangouei, P; Elder, JM; Burke, N; Hall, A; Hausenloy, DJ
Abstract: Background: Ischaemic heart disease is the major cause of morbidity and mortality worldwide. Novel therapeutic strategies are essential to protect the heart from acute ischaemia-reperfusion injury (IRI). It has been reported that inhibiting mitochondrial fission, protects the heart against cardiomyocyte death during acute IRI. We investigated the mitochondrial fission proteins, MiD49 and MiD51, as novel targets for cardioprotection, Methods and Results: Genetic ablation of both MiD49 and MiD51 in HL-1 cardiac cells (a murine atrial-derived cell line), using shRNAs had the following effects: (1) A significant increase in the proportion of cells expressing predominantly elongated mitochondria (81.5±2.9% MiD49+MiD51 knockdown vs. 49.4±4.9% vector control: n=120 cells/group; P<0.05); (2) It led to a delay in time taken to induce mitochondrial permeability transition pore (MPTP) opening (485±61 seconds MiD49+MiD51 knockdown vs. 233±20 seconds vector control: n=120 cells/group; P<0.05); (3) Cell death following simulated IRI was reduced (27.9±3.0% MiD49+MiD51 knockdown vs. 56.7±2.4% vector control: n=300 cells/group; P<0.05). Interestingly, the individual knockdown of either MiD49 or MiD51 alone had no effect on these parameters. Unexpectedly, the over-expression of either MiD49 or MiD51 had similar beneficial effects: (1) The formation of abnormally elongated (hyperfused) mitochondria with a peri-nuclear distribution; (2) It delayed the induction of MPTP opening (339±23 seconds MiD49 over-expression, 336±19 seconds MiD51 over-expression vs. 208±16 seconds vector control: n=120 cells/group; P<0.05); (3) It reduced cell death following simulated IRI (21.5±3.7% MiD49 over-expression, 20.0±3.7% MiD51 over-expression vs. 52.0±4.6% vector control: n=300; P<0.05). The explanation for this apparent beneficial effect with MiD49 or MiD51 over-expression, may be due to Drp1 sequestration to mitochondria, leading to unopposed abnormal mitochondrial elongation (hyperfusion). Conclusions: Here we show that combined knockdown of the newly discovered mitochondrial fission proteins, MiD49 and MiD51, induced mitochondrial elongation, delayed MPTP opening, and protected cells against simulated acute IRI, implicating MiD49 and MiD51 as novel targets for cardioprotection. Unexpectedly, the over-expression of these fission proteins induced a state of abnormal hyperfusion, delayed MPTP opening, and protected cells against simulated acute IRI.